Pancreas transplant rejection episodes are not revealed by biopsies of the donor duodenum in a prospective study with paired biopsies. Issue 5 (3rd February 2018) - Nordheim, E.; Horneland, R.; Aandahl, E. M.; Grzyb, K.; Aabakken, L.; Paulsen, V.; Midtvedt, K.; Hartmann, A.; Jenssen, T.
Abstract : The surgical technique with duodeno‐duodenal enteroanastomosis of pancreas transplants allows for representative endoscopic ultrasound‐guided needle biopsies of the donor duodenum and the pancreas graft. We assessed whether histological findings in transplanted donor duodenal biopsies can indicate rejection in the transplanted pancreas. Since September 2012, a duodeno‐duodenal enteroanastomosis has been the default technique for pancreas transplantations at our center. In 67 recipients we prospectively examined 113 endoscopic ultrasound‐guided procedures with representative biopsies from the duodenum grafts and the pancreas grafts (97 per protocol and 16 on indication). All graft biopsies were evaluated according to established rejection criteria. A total of 22 biopsy‐proven pancreas rejections were detected, with 2 matching duodenal biopsies showing rejection. This gives a sensitivity of 9% for detection of a pancreas rejection by duodenal biopsies. The other matching duodenal biopsies were either normal (n = 13) or indeterminate (n = 7). Rejection of the donor duodenum was found in only 6/113 biopsies, with 2 concurrent pancreas rejections. In conclusion, the donor duodenum is not a useful reporter organ for rejection in the pancreas graft. Abstract : Duodenal cuff biopsies reveal only one‐tenth of pancreas rejection episodes in this prospective study with paired biopsies, thus casting doubt on the duodenum graft as an adequate reporter organ for pancreas rejection.